1994
DOI: 10.3109/00365529409094890
|View full text |Cite
|
Sign up to set email alerts
|

Omeprazole plus Amoxicillin for Cure of Helicobacter pylori Infection Factors Influencing the Treatment Success

Abstract: Several patient- and therapy-related factors diminish or increase the rate of H. pylori cure obtained by omeprazole/amoxicillin. These should be considered in future studies comparing different treatment regimens for curing H. pylori infection and also when designing treatment regimens applicable for routine clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
98
4
3

Year Published

1996
1996
2002
2002

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(111 citation statements)
references
References 13 publications
6
98
4
3
Order By: Relevance
“…3 Our relatively good results may have been in part related to the overall good compliance. 5,28 However, the upper level of the 95% con®dence limits in this study was only 80%, with marked differences between smokers and non-smokers. Because of the overall low success rate, we do not plan to compare this therapy to others.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…3 Our relatively good results may have been in part related to the overall good compliance. 5,28 However, the upper level of the 95% con®dence limits in this study was only 80%, with marked differences between smokers and non-smokers. Because of the overall low success rate, we do not plan to compare this therapy to others.…”
Section: Discussioncontrasting
confidence: 65%
“…These results are consistent with studies using dual therapy containing omeprazole and amoxycillin. 28,30 Although the effect of smoking on the combination of three drugs we used is not known, the fact that smoking had a major effect suggests that the addition of metronidazole was unable to overcome this problem. No detrimental effect of smoking was seen with omeprazole plus clarithromycin, 31 emphasizing the importance of analysing the results of studies with lower than expected cure rates in relation to smoking history.…”
Section: Discussionmentioning
confidence: 99%
“…Incidence of adverse events caution, it has been coincidentally demonstrated in previous work. 6 It has also been shown that lower intragastric acidity is a predictor of successful eradication 7 and this mechanism has been previously proposed to explain the effect of age on eradication success. Although this study has shown that 5-day LCM gives a higher overall eradication rate, it appears to be less effective than a 7-day LCM regimen, especially against metronidazole-resistant strains.…”
Section: Discussionmentioning
confidence: 99%
“…4 Similarly, in an analysis of various studies advanced age was, among others, a signi®cant independent factor in predicting treatment success. 5 As this retrospective analysis was based on different treatment schedules and patient characteristics, we decided to perform a single-blind comparative study where H. pylori-positive patients were also prospectively matched for age. In addition, as in previous studies, 3±5 compliance was regarded as a major determinant, but only assessed by unreliable pill count or interview, and plasma levels of all applied drugs were monitored.…”
Section: Discussionmentioning
confidence: 99%